Preoperative Grading of Sacrococcygeal Teratoma: A Roadmap to Successful Resection - Amr Abdelhamid Abouzeid; Shaimaa Abdelsattar Mohammad; Mohammed Elsherbeny; Nehal A Radwan; Osama El-Naggar (EL-Med-Pub, 2017)
Purpose: to include the most relevant preoperative imaging features of sacrococcygeal teratoma (SCT) in a grading system that would provide guidance to surgeons during excision of such rare tumors. Patients and Methods: The medical records of patients with SCT, who were managed at our hospital during the period 2009 through 2016, were retrospectively reviewed. Only cases of SCT with available preoperative cross-sectional imaging studies (MRI and/or CT scans) were included in the study. The preoperative imaging features were correlated to the operative and pathological findings. Results: The study included 24 cases of SCT (20 females and 4 males). Their age at presentation ranged from day one to 36 months. The following were identified as relevant preoperative imaging features to be included in our proposed grading system: tumor size, level of deep extension of the tumor, and tumor consistency. Among predominantly cystic SCT, a special subtype C3 could be identified with its characteristic irregular internal cyst wall thickening caused by the in-growth of solid tumor component. These cases were always associated with immature pathology. Conclusion: MRI is a useful modality in the preoperative assessment of cases of SCT by providing a grading system that can indicate for the prognosis and degree of expected surgical challenge.